A new Sasanian helmet in the Musee d’Art Classique de Mougins - AHMAD, Shah Nadeem (Historia i Świat, 2015)
This article will describe a previously unknown helmet in the Musee d’Art Classique de Mougins (MACM) in southern France. The helmet is of the “bandhelm” variety and is decorated with heraldic motifs plus silvered rivets. The helmet bears some resemblance to known helmets from Cheragh Ali Tepe / Amlash but also differs in several crucial ways. In the light of this new example, a new typology of Sasanian helmets and some novel insights on the development of Sasanian helmets is also offered.